2018
DOI: 10.1038/s41598-018-19408-9
|View full text |Cite
|
Sign up to set email alerts
|

A synthetic combinatorial approach to disabling deviant Hedgehog signaling

Abstract: Mutations in components of the Hedgehog (HH) signal transduction pathway are found in the majority of basal cell carcinoma (BCC) and medulloblastoma incidents. Cancerous cells with intrinsic or acquired resistance to antagonists targeting the seven transmembrane effector Smoothened (SMO) frequently invoke alternative mechanisms for maintaining deviant activity of the GLI DNA binding proteins. Here we introduce a chemical agent that simultaneously achieves inhibition of SMO and GLI activity by direct targeting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Finally, as VPA and TSA, vorinostat modulates SMAD4 localization and Nocth3 expression [64,65], but Fan and colleagues also showed that a small molecule SMO-HDAC antagonist was able to retain inhibitory activity for Gli transcription induced in SMO-dependent and SMO-independent ways [66]. Furthermore, TSA and domatinostat, two specific class I and II HDAC inhibitors, switched off Gli signaling by downregulating a transcriptional factor of FoxM1 [67] in the first case and by inhibition of HDAC1/2/3 in the second case [68].…”
Section: Histone Deacetylase (Hdac) Inhibitors Target Cancer Stem mentioning
confidence: 99%
“…Finally, as VPA and TSA, vorinostat modulates SMAD4 localization and Nocth3 expression [64,65], but Fan and colleagues also showed that a small molecule SMO-HDAC antagonist was able to retain inhibitory activity for Gli transcription induced in SMO-dependent and SMO-independent ways [66]. Furthermore, TSA and domatinostat, two specific class I and II HDAC inhibitors, switched off Gli signaling by downregulating a transcriptional factor of FoxM1 [67] in the first case and by inhibition of HDAC1/2/3 in the second case [68].…”
Section: Histone Deacetylase (Hdac) Inhibitors Target Cancer Stem mentioning
confidence: 99%
“…For example, itraconazole is believed to be a good candidate for second generation therapy against Hh-driven cancers [ 108 ]. Additionally, combinatorial approaches targeting both Smo and downstream signalling molecules have been recognised as promising in cancer treatment [ 109 ]. Targeting regulatory mechanisms of Smo presents another therapeutic approach for acquired resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study shows that the activity of Hedgehog pathway is largely independent of Smo and therefore inherently resistant to Smo inhibitors in AML, and hypomethylating agent improves glasdegib sensitivity by increasing the level of Gli-3 repressor and modulation of Gli-1 [ 71 ]. HDAC inhibitors abrogate Smo-dependent and Smo-independent GLI activation and Hedgehog-targeted gene expression and overcome drug resistance to Smo inhibitors in cancer cells [ 72 , 73 ]. Combinatorial inhibition of HDACs and Hedgehog pathway synergistically suppresses tumor growth and homologous recombination in aerodigestive cancers, and a dual-targeted inhibitor is capable of effectively overcoming the Smo inhibitor resistance conferred by Smo mutations [ 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%